Conectando Conservação Ambiental e Cultura Paraense por meio do Jogo Tekohá - Shibata, Nina Niwa; Castro, Pedro M. D. de; Albuquerque, Davi de Souza; Cruz, Laura Pereira; Lima, Mayara Silva de; Soares, Bryan Young Carvalho; Alves, Carolina de Lima; Quaresma, Thaís Martins; Oliveira, Sandro Ronaldo Bezerra (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento Digital, 2025)
Introduction: Games are entertainment tools that have a significant impact on modern culture. They are a necessary condition for the cultural consolidation of a society. Objective: In this context, this paper aims to present the cultural context of the Tekohá game, created to raise awareness among players about environmental preservation, in line with the COP30 event. Methodology: The game is inspired by Pará’s cultural heritage, incorporating elements such as Brazilian folklore legends, native animals, and traditional cuisine. Results: Relevant data on environmental issues affecting the municipalities featured in the game were collected, along with information on local culture, local cuisine, and other regional customs.